1997
DOI: 10.3109/01674829709080688
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychological factors on the outcome of the fertilization step of invitrofertilization

Abstract: Our objective was to determine whether psychological factors have an influence on the outcome of the fertilization step of in vitro fertilization (IVF) trials. The design was a prospective cohort study. We studied 48 women and 32 of their spouses. Each subject was assessed psychologically on the day before oocyte retrieval (OR) with the Child Project Questionnaire (CPQ) and the Ways of Coping Checklist. In addition, the State-Trait Anxiety Inventory was filled in by subjects 2 days before OR, and the State for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
1
19
0
3
Order By: Relevance
“…In this study compulsion and paranoia are very prominent in all four groups and they are mainly the most important factors in anxiety level in the HI male and their partners. Infertility in addition to the length on infertility was an important factor in causing anxiety in the partners of HI males, which was again consistent with previous reports [13][14][15][16]. Having the knowledge of infertility in the SCI male and their partners and the social support are some of the important factor that make these groups vary in their presentations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study compulsion and paranoia are very prominent in all four groups and they are mainly the most important factors in anxiety level in the HI male and their partners. Infertility in addition to the length on infertility was an important factor in causing anxiety in the partners of HI males, which was again consistent with previous reports [13][14][15][16]. Having the knowledge of infertility in the SCI male and their partners and the social support are some of the important factor that make these groups vary in their presentations.…”
Section: Discussionsupporting
confidence: 90%
“…Psychological problems including anxiety that follow these events have a serious impact on the patients' lives. Although a trauma or an event is essential in developing PTSD but the individuals emotional status, social, familial and cultural believes have an important impact [6,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A series of psychological questionnaires was presented and measures from these instruments were correlated with ratings of the Assess_Mind to assess the construct validity of the scales. We presented the Child Project Questionnaire (CPQ), a self-report questionnaire previously developed and validated by our group, that is used to measure specifi c psychological factors that may contribute to the etiology of infertility (Stoléru et al, 1993;Stoléru et al, 1997). The CPQ covers three domains: (i) the wish to have a child, but also anxieties related to the prospect of having a child/becoming a parent; (ii) qualitative and quantitative aspects of sexual life; and (iii) family history related to procreation.…”
Section: Other Psychological Measuresmentioning
confidence: 99%
“…Two types of score are derived from the CPQ: (i) a priori scores, derived on a conceptual basis by summing items related to the same dimensions; these are the scores of Anxieties Associated with Prospective Parenthood (AAPP), the score of Diffi culties in Family History related to Procreation, and the score of Sexual Diffi culties; (ii) factor scores, derived from factor analysis. Separate factor analyses have been performed for women and men undergoing IVF treatment and have yielded two interpretable factors for women and one for men (Stoléru et al, 1997). In both women and men, Factor I has been interpreted as a measure of the Wish to Have a Child.…”
Section: Other Psychological Measuresmentioning
confidence: 99%
“…Some interview-based studies (Vartiainen et al, 1994;Stoleru et al, 1997;Eugster et al, 2004), but not all (Harlow et al, 1996;Milad et al, 1998), have shown that psychological stress results in adverse outcomes of IVF -ET. Furthermore, infertility itself aggravates psychological stress (Campagne, 2006;Cousineau and Domar, 2007).…”
Section: Introductionmentioning
confidence: 99%